Students’ ICT literacy and conceptual knowledge correlation: from a genetic course and a gender perspective - Dewi Murni; Sri Rahayu Lestari; Sri Endah Indriwati; Siti Zubaidah; Hendra Susanto; Paidi Paidi (International Journal of Evaluation and Research in Education (IJERE), 2024)
The correlation between students’ information communication technology (ICT) literacy and conceptual knowledge from a gender perspective is essential to understanding the causal effects of student learning. Therefore, this study aimed to describe the relationship between students’ ICT literacy and conceptual knowledge in a genetics course, especially from a gender perspective. This study employed a descriptive research method that used randomized sampling. The instruments used were conceptual knowledge and ICT literacy test sheets. The data were analyzed by using analysis of variance (ANOVA) and Pearson correlational statistics. The results showed male students have higher ICT literacy than females. Otherwise, male students have a lower conceptual knowledge than females. Furthermore, male students’ ICT literacy and conceptual knowledge showed a strong relationship, while female students showed a weak relationship. The findings support the idea that integrating ICT into genetics curricula might help students develop their ICT literacy and conceptual knowledge more effectively, especially female students.